Catalytic synthesis of 9-cis-retinoids: mechanistic insights. Issue 28 (20th June 2019) - Kahremany, Shirin; Kubas, Adam; Tochtrop, Gregory P.; Palczewski, Krzysztof
Abstract : Novel approach for the catalytic synthesis of 9- cis -retinoids using conventional heat and microwave irradiation, followed by mechanistic investigation using quantum chemical calculations at the level of coupled-cluster methods. Abstract : The regioselective Z -isomerization of thermodynamically stable all- trans retinoids remains challenging, and ultimately limits the availability of much needed therapeutics for the treatment of human diseases. We present here a novel, straightforward approach for the catalytic Z -isomerization of retinoids using conventional heat treatment or microwave irradiation. A screen of 20 transition metal-based catalysts identified an optimal approach for the regioselective production of Z -retinoids. The most effective catalytic system was comprised of a palladium complex with labile ligands. Several mechanistic studies, including isotopic H/D exchange and state-of-the-art quantum chemical calculations using coupled cluster methods indicate that the isomerization is initiated by catalyst dimerization followed by the formation of a cyclic, six-membered chloropalladate catalyst–substrate adduct, which eventually opens to produce the desired Z -isomer. The synthetic development described here, combined with thorough mechanistic analysis of the underlying chemistry, highlights the use of readily available transition metal-based catalysts in straightforward formats for gram-scale drug synthesis.